The point radiation defects in Li₆YB₃O₉:Eu³⁺ single crystals - Yavetskiy, R.P. (Functional Materials, 2008)
The point radiation defects in Li₆YB₃O₉:Eu³⁺ single crystals have been studied. The irradiation of Li₆YB₃O₉:Eu³⁺ single crystals with beta particles has been found to cause a valence state change (Eu³⁺ -> Eu²⁺) in some fraction of europium ions being detected by decrease of Eu³⁺ photoluminescence integral intensity, as well as formation of O⁻ hole centers resulting in appearance of a radiation induced broad absorption band in the λ = 320-500 nm range. Two models of hole centers in Li₆YB₃O₉:Eu³⁺ crystals (O⁻ isolated ion or BO₃²⁻ complex ion) have been proposed.